Whole Object Assumption and Mutual Exclusivity Assumption in 3-4-Year-Old Cebuano Preschoolers: A Qualitative Analysis - Laput, Daylinda Luz Reluya (Journal of English Language Teaching and Linguistics, 2017)
The whole object assumption (WOA) and mutual exclusivity (ME) assumption proposed by Markman (1990) are constraints children use in word learning. This small-scale psycholinguistic study investigates the constraints function in 14 preschoolers at ages 3 and 4 using WOA and ME in deciphering part labels. Using quasi-experimental method, children identified objects and animals. Findings show that while WOA is still used by the participants ME overrides. Further findings reveal no evidence of the claim that older participants used ME better than the younger ones. However, gender seems to play an important role in the participants’ performance for boys did much better than girls in the experiments. Thus, the result recommends further future research on the relation between the two constraints on word learning (WOA and ME) and age and gender. However, this study found two limitations: the drawings and the questions used in the study may fail to fully reveal the children’s ability since previous studies offer non-standard materials and procedure used in their experiments; and the study itself, is regarded as small-scale. Therefore, the research findings can hardly be generalized. Nevertheless, the research at least presents how the Cebuano speaking preschoolers learned new words via WOA and ME assumption.